Levels of Thyroid Peroxidase Antibodies is Higher in Threatened Abortion - Sanjaya, I Nyoman A.; Hidayat, Syarif T (Indonesian Socety of Obstetrics and Gynecology, 2013)
Objective: To assess the relationship between the incidence of threatened abortion with serum levels of TPO antibodies. Methods: This was cross-sectional study involving subjects 40 cases and 40 controls. The study was conducted September 2012 to November 2012. The difference in the levels of thyroid peroxidase antibody was tested by Mann-Whitney test. Result: In this study, hypothyroidism was found only in the abortion group, as many as 6 subjects (15%) and subclinical hypothyroidism was more prevalent in threatened abortion group, found in 2 people (5%), compared to normal pregnant group, found in only 1 person (2.5%). This study revealed a significant difference in the mean levels of TPO antibodies in the threatened abortion and normal pregnancy group. The mean levels of TPO antibodies in threatened abortion group was 91.76 ± 133.18 IU/ml with the lowest level of 14.41 IU/ml and the highest levels of 534.47 IU/ml while in the normal pregnancy group found an average 12.97 ± 3.91 IU/ml with the lowest value 2.02 IU/ml and the highest value of 20.78 IU/ml. In this study, subjects with TPO antibody levels ≥ 125 IU/ml, all of them experienced threatened abortion (n = 7) and found the risk of miscarriage by 2.212-fold compared with subjects with TPO levels < 125 IU/ml. Conclusion: There are differences in the levels of TPO antibodies in patients with threatened abortion and in normal pregnancies, with average levels of TPO antibodies in imminent abortion group is higher than normal pregnancy group. There is a relationship between TPO antibody levels ≥ 125 IU/ml with the incidence of threatened abortion, with the risk of threatened abortion increasing 2.212 times. [Indones J Obstet Gynecol 2013; 1-3: 134-8] Keywords: threatened abortion, thyroid peroxidase antibody (TPO)